Introducing Global Issues in A Language Classroom: Knowing Other Cultures by Analysing Multimodal Texts from NGOs - María Martínez Lirola (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2018)
This article shows the importance of teaching with texts from Non-Governmental Organizations (NGOs) in which women from other cultures are represented in order to bring global issues in a language classroom and to deepen in the visual representation of women from other cultures so that students develop their gender perspective. Our main objectives with the research presented in this paper are to introduce students to visual grammar and to work with texts that allow students at tertiary level develop critical thinking and respect for cultural diversity, which will contribute to the introduction of global issues into the classroom. Kress and van Leewen (2006) model of visual grammar was introduced in an English language course at University level so that students could read and analyse multimodal texts. Having done this, students were asked to analyse the texts in groups in order to observe the importance of visuals in the construction of meaning and the way in which the women represented appeared portrayed. The analysis using visual grammar shows that the texts under analysis portray a positive image of African women, which breaks the traditional stereotypes of these women being weak, dependent and marginalised. In addition, this research will show that teaching global issues using multimodal texts from the NGO Intermón Oxfam will help students understand how the discourse used by NGOs creates meaning through different visual and linguistic choices.